Assessing The Impact of Covid-19 Pandemic on Domestic Violence in Kabale Municipality Kabale District. - Ruhinda, Irene George (Kabale University, 2024)
The study was about the impacts of COVID-19 on domestic violence in Kabale district. The study was guided by objectives like assessing the extent of the occurrences of domestic violence during and after the lockdown in the Kabale district, finding remedies to mitigate the rate of domestic violence during and after the lockdown in the Kabale District, and suggesting further remedies to reduce the occurrence and effects of domestic violence on society and the economy in Kabale district. The study sampled 96 respondents out of 99 as the target population. A descriptive design was used in the study. The researcher used both Primary and secondary data. Secondary data was collected from documents and policies. Literature was reviewed using secondary data sources including other reports, journals, the internet, research projects, and information from the University library. The study also found that domestic violence is increasingly seen as a 'shadow pandemic' to COVID-19. Domestic violence escalates during times of crisis, including epidemics. There is a need to increase efforts to raise massive social awareness of the criminal nature of domestic violence and the services available to victims. This should be done in the form of seminars, workshops, and massive sensitization over both traditional and social media platforms such as radios, television, Facebook, YouTube, and other media platforms. Some mentioned that leads to unintended pregnancies, induced abortions, gynecological problems, and sexually transmitted infections, including HJV. Intimate partner violence in pregnancy also increases the likelihood of miscarriage, stillbirth, pre-term delivery, and low birth weight babies. The study concludes that Lockdown is especially likely to have led to episodes of first-time abuse: the increase from neighborhoods with no recent history of violence was roughly double the increase from neighborhoods with a recent history of violence. The study recommends that there is a need for empowerment directed at vulnerable and socially excluded domestic violence survivors is ideal as it might help women gain control of their lives and instill in them motivation to reclaim their position in the community. Women urgently need better child-care alternatives and a wider range of income-generation and employment opportunities from which they may obtain incomes equal to those of men.